hubungan Hubungan Pengetahuan Makanan Jajanan dengan Kejadian Diare pada Siswa SD Negeri Setu Kota Tangerang Selatan - Abul A'la Al Maududi; Miftah Hasana Lubis (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Diarrhea is an infectious disease and is characterized by symptoms such as changes in the shape and consistency of stools to become soft to liquid with a frequency of 3 times or more urination accompanied by vomiting. According to UNICEF data (2013), if viewed globally, diarrhea is a disease with a high degree of pain and mortality, especially in developing countries, and is also one of the three leading causes of child death globally. In Tangerang South in the data of the Performance Report of Government Institutions (LKIP), the number of patients suffering from diarrhea in 2020 reached 22.539 cases with the top 5 rank. The purpose of this research is to know the relationship between knowledge and behavior of food consumption and the occurrence of diarrhea in SDN Setu City Tangerang South. The Research Method uses quantitative research using the Cross-Sectional approach with 72 respondents. The results of this study show no significant relationship between knowledge with diarrhea occurrence with chi-square test results at get p-value 0.848 (p>0,05) and no significant relation to behavior with diary occurrence in get p-value 0.164 (p >0,05). It can be concluded that there is no significant link between knowledge and behavior with euthanasia food consumption to the occurrence of diarrhea in children at the State School of Setu City Tangerang South. The advice that the researchers can give to the school is that it is recommended to organize diarrhea-related education and wash hands with soap with 7 steps. As well as making a canteen in a school or a healthy cantina.